[https://crypto.stanford.edu/pbc/notes/group/group.html].
We define a group
- For all
$x, y \in G, x \cdot y \in G$ . This is normally referred to as 'algebraic closure'. - There exist an identity element
$1 \in G$ such that$x \cdot 1 = x$ for all$x \in G$ . - The operation defined
$(\cdot)$ is associative, that is, for all$x, y, z \in G$ we have$x(yz) = (xy)z$ . - For all
$x \in G$ there exists an element$x^{-1}$ with$xx^{-1} = x^{-1}x = 1$ (the inverse). I proved this property here [https://github.com/Z323323/From-Fermat-to-the-group-theory?tab=readme-ov-file#proof-of-existence-and-uniqueness-of-inverses-in-z_p-and-z_phinast]. Note also that the formal definition of group doesn't imply we have a finite group and it's therefore more general. The linked proof is about finite multiplicative groups, which are the main interest for computer scientists.
- If only
$1,3$ holds for$G^{*}$ then$G^{\ast}$ is a semi-group. - If only
$1, 2, 3$ holds for$G^{*}$ then$G^{\ast}$ is a monoid.
In general if you see
If
- For all
$x, y \in G, xy = yx$
and we call it abelian.
- Closure (not really trivial if you played around with Zn.py using
$n$ non-prime). - Associativity (trivial).
- Right and left cancellation:
-
$ax = bx$ iff$a = b$ . This one is not that trivial if you think about finite groups and therefore modular arithmetic [https://github.com/Z323323/From-Fermat-to-the-group-theory?tab=readme-ov-file#cancellation-law].
-
The order of an element
A subset
We can write
An homomorphism is a map
for all
Let's clarify this concept, since it looks really abstract, and it is indeed, and it's also really important in math.
First thing to understand is the meaning of map, and the different kinds of map in mathematics.
-
map = function. A function is a map which associates elements from a set (domain) to some elements of another set (codomain). The actual elements mapped will be elements
$\in$ codomain, which are called image of the function/map, and so we could have image = codomain or not.
-
A map/function has
$2$ foundation constraints which defines it.- It can't have two mappings starting from the domain, it's exactly one map for every element of the domain, while it can for example has two elements which map the same element of the codomain/image.
- Every element of the domain must be mapped (it's not true for the codomain).
-
A map/function has different properties which define it's structure, it can be
- surjective: every element of the codomain is mapped.
-
injective: every element of the domain maps
$1$ and only$1$ element of the codomain. - bijective: if it's both surjective and injective.
Now let's get back to our omomorphism definition. An omomorphism is a particular mapping/function where its definition holds, that is, where the mapping
Here lie a couple behaviours which could not be straightforward at first sight, we can see that there are two implied relations
and because that relation (binary operation) will be defined individually for elements which belong to
Imagine the infinite group
We define the omomorphism
which holds since [https://github.com/Z323323/From-Fermat-to-the-group-theory?tab=readme-ov-file#multiplication-property].
This means that the multiplicative group of positive integers is omomorphic to the multiplicative group of positive integers
Now, since our focus will be directed towards finite multiplicative groups let's analyze the definition of homomorphism for two general finite groups
We can see that for multiplicative groups we can avoid the construction regarding the binary operator and just consider the modulo, then we define the omomorphism
Note that when reasoning about multiplicative subgroups the previous form simplifies because the modulo is shared, and for example
If
If
This theorem could look very strange at first, you should note that we are making an abstraction considering
We can easily replace
A non-empty subset
A non-empty subset
For a subgroup
For any set
A non-empty subset
Let
Analyzing
Let
where
Let
Let
and we can define the general form for every element of
[https://crypto.stanford.edu/pbc/notes/group/lagrange.html].
Let
Let
Under this result we can easily see that
and under
which is always true since
If
The first statement derives directly from the general form for subgroups elements I wrote previously and
The second statement holds because, recalling the general form for the elements of
which is the general form for the elements of
Let
Let
It is worth to spend a couple words on additive finite groups now. To define them we can just take the definition of multiplicative subgroups and change the identity element to
Defining
$\{1, 2, 3, 4, 5, 0, \dots \}$ $\{2, 4, 0, 2, 4, 0, \dots \}$ $\{3, 0, 3, 0, 3, 0, \dots \}$ $\{4, 2, 0, 4, 2, 0, \dots \}$ $\{5, 4, 3, 2, 1, 0, \dots \}$
and we can derive a couple of simple properties. We have
$a \cdot bc \equiv 0 \mod abc$ $ab \cdot c \equiv 0 \mod abc$ $d \cdot abc \equiv 0 \mod abc$ $aa \cdot bc \equiv 0 \mod abc$ $ad \cdot bc \equiv 0 \mod abc$ $abd \cdot c \equiv 0 \mod abc$ $de \cdot abc \equiv 0 \mod abc$
where numbers on the left side of
We can now state a couple rules.
Every subgroup of a cyclic group is cyclic, and this works both for additive and multiplicative finite groups. This doesn't need a proof, since everything said.
Every group which has composite order have proper subgroups. This doesn't need a proof either.
Note that since the course analyzed is a general course on group theory a lot of things could become quite strange just because the definition of group, as we saw earlier, admits various interpretations. Since as I already mentioned we are mainly interested in finite groups, theorems will normally refer to finite multiplicative groups and finite additive groups which we are going to combine together from now on.
If each element
Considering the scenario of the lemma proposed, the isomorphism for
and each element of
Since [https://github.com/Z323323/Group-theory-elements?tab=readme-ov-file#theorem] we know that
that is, every element has order
which is quite unbelievable at first, that is, since
$(0, 0) + X = X$ $(1, 0) + (0, 1) = (1, 1)$ $(1, 0) + (1, 1) = (0, 1)$ $(0, 1) + (1, 0) = (1, 1)$ $(0, 1) + (1, 1) = (1, 0)$ $(1, 1) + (1, 0) = (0, 1)$ $(1, 1) + (0, 1) = (1, 0)$
and
and
unbelievable right? And it's not over because since the maps
$1 ↔ (0, 0)$ $3 ↔ (1, 0)$ $5 ↔ (0, 1)$ $7 ↔ (1, 1)$
we have
$(0, 0) + X = X$ $(1, 0) + (0, 1) = (1, 1) ↔ 3 \cdot 5 \mod 8 = 7$ $(1, 0) + (1, 1) = (0, 1) ↔ 3 \cdot 7 \mod 8 = 5$ $(0, 1) + (1, 0) = (1, 1) ↔ 5 \cdot 3 \mod 8 = 7$ $(0, 1) + (1, 1) = (1, 0) ↔ 5 \cdot 7 \mod 8 = 3$ $(1, 1) + (1, 0) = (0, 1) ↔ 7 \cdot 3 \mod 8 = 5$ $(1, 1) + (0, 1) = (1, 0) ↔ 7 \cdot 5 \mod 8 = 3$
Let's now analyse
This case introduces some complexity, because since the
$3 ↔ (0, 1)$ $7 ↔ (2, 2)$ $->$ $3^2 \mod 16 = 9 ↔ (0, 1) + (0, 1) = (0, 2)$ $3^3 \mod 16 = 11 ↔ (0, 2) + (0, 1) = (0, 3)$ $3^4 \mod 16 = 1 ↔ (0, 3) + (0, 1) = (0, 0)$ $and$ $7^{2} \mod 16 = 1 ↔ (2, 2) + (2, 2) = (0, 0, 0)$ $then$ $3 \cdot 7 \mod 16 = 5 ↔ (0, 1) + (2, 2) = (2, 3)$ $3^{2} \cdot 7 \mod 16 = 15 ↔ (0, 2) + (2, 2) = (2, 0)$ $3^{3} \cdot 7 \mod 16 = 13 ↔ (0, 3) + (2, 2) = (2, 1)$ $also$ $5^{2} \mod 16 = 9 ↔ (2, 3) + (2, 3) = (0, 2)$ $5^{3} \mod 16 = 13 ↔ (0, 2) + (2, 3) = (2, 1)$ $9^{2} \mod 16 = 1 ↔ (0, 2) + (0, 2) = (0, 0)$ $13^{2} \mod 16 = 9 ↔ (2, 1) + (2, 1) = (0, 2)$ $13^{3} \mod 16 = 5 ↔ (0, 2) + (2, 1) = (2, 3)$ $13^{4} \mod 16 = 1 ↔ (2, 3) + (2, 1) = (0, 0)$ $15^{2} \mod 16 = 1 ↔ (2, 0) + (2, 0) = (0, 0)$
so
$1 ↔ (0, 0)$ $3 ↔ (0, 1)$ $5 ↔ (2, 3)$ $7 ↔ (2, 2)$ $9 ↔ (0, 2)$ $11 ↔ (0, 3)$ $13 ↔ (2, 1)$ $15 ↔ (2, 0)$
Let's finally define the isomorphism
Honestly I don't know if it is possible to derive a simpler/different isomorphism but my construction seems to work incredibly. Another interesting and strange behaviour of this kind of isomorphism is that it will hold for
where
$2 ↔ (0, 1)$ $11 ↔ (2, 2)$ $->$ $2^2 \mod 15 = 4 ↔ (0, 1) + (0, 1) = (0, 2)$ $2^3 \mod 15 = 8 ↔ (0, 2) + (0, 1) = (0, 3)$ $2^4 \mod 15 = 1 ↔ (0, 3) + (0, 1) = (0, 0)$ $and$ $11^{2} \mod 15 = 1 ↔ (2, 2) + (2, 2) = (0, 0)$ $then$ $2 \cdot 11 \mod 15 = 7 ↔ (0, 1) + (2, 2) = (2, 3)$ $2^{2} \cdot 11 \mod 15 = 14 ↔ (0, 2) + (2, 2) = (2, 0)$ $2^{3} \cdot 11 \mod 15 = 13 ↔ (0, 3) + (2, 2) = (2, 1)$ $also$ $4^{2} \mod 15 = 1 ↔ (0, 2) + (0, 2) = (0, 0)$ $7^{2} \mod 15 = 4 ↔ (2, 3) + (2, 3) = (0, 2)$ $7^{3} \mod 15 = 13 ↔ (0, 2) + (2, 3) = (2, 1)$ $7^{4} \mod 15 = 1 ↔ (2, 1) + (2, 3) = (0, 0)$ $8^{2} \mod 15 = 4 ↔ (0, 3) + (0, 3) = (0, 2)$ $8^{2} \mod 15 = 2 ↔ (0, 2) + (0, 3) = (0, 1)$ $8^{2} \mod 15 = 1 ↔ (0, 3) + (0, 1) = (0, 0)$ $9^{2} \mod 15 = 1 ↔ (0, 2) + (0, 2) = (0, 0)$ $13^{2} \mod 15 = 4 ↔ (2, 1) + (2, 1) = (0, 2)$ $13^{3} \mod 15 = 7 ↔ (0, 2) + (2, 1) = (2, 3)$ $13^{4} \mod 15 = 1 ↔ (2, 3) + (2, 1) = (0, 0)$ $14^{2} \mod 15 = 1 ↔ (2, 0) + (2, 0) = (0, 0)$
As you can see this construction is from a structural point of view the same we made for
Generalizing we can observe that for
To conclude,
Let's now define the isomorphism
$2 ↔ (\{ 0, 0 \}, \{ 0, 1 \})$ $11 ↔ (\{ 1, 0 \}, \{ 1, 0 \})$ $->$ $2^2 \mod 15 = 4 ↔ (\{ 0, 0 \}, \{ 0, 1 \}) + (\{ 0, 0 \}, \{ 0, 1 \}) = (\{ 0, 0 \}, \{ 1, 0 \})$ $2^3 \mod 15 = 8 ↔ (\{ 0, 0 \}, \{ 1, 0 \}) + (\{ 0, 0 \}, \{ 0, 1 \}) = (\{ 0, 0 \}, \{ 1, 1 \})$ $2^4 \mod 15 = 1 ↔ (\{ 0, 0 \}, \{ 1, 1 \}) + (\{ 0, 0 \}, \{ 0, 1 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$ $and$ $11^{2} \mod 15 = 1 ↔ (\{ 1, 0 \}, \{ 1, 0 \}) + (\{ 1, 0 \}, \{ 1, 0 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$ $then$ $2 \cdot 11 \mod 15 = 7 ↔ (\{ 0, 0 \}, \{ 0, 1 \}) + (\{ 1, 0 \}, \{ 1, 0 \}) = (\{ 1, 0 \}, \{ 1, 1 \})$ $2^{2} \cdot 11 \mod 15 = 14 ↔ (\{ 0, 0 \}, \{ 1, 0 \}) + (\{ 1, 0 \}, \{ 1, 0 \}) = (\{ 1, 0 \}, \{ 0, 0 \})$ $2^{3} \cdot 11 \mod 15 = 13 ↔ (\{ 0, 0 \}, \{ 1, 1 \}) + (\{ 1, 0 \}, \{ 1, 0 \}) = (\{ 1, 0 \}, \{ 0, 1 \})$ $also$ $4^{2} \mod 15 = 1 ↔ (\{ 0, 0 \}, \{ 1, 0 \}) + (\{ 0, 0 \}, \{ 1, 0 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$ $7^{2} \mod 15 = 4 ↔ (\{ 1, 0 \}, \{ 1, 1 \}) + (\{ 1, 0 \}, \{ 1, 1 \}) = (\{ 0, 0 \}, \{ 1, 0 \})$ $7^{3} \mod 15 = 13 ↔ (\{ 0, 0 \}, \{ 1, 0 \}) + (\{ 1, 0 \}, \{ 1, 1 \}) = (\{ 1, 0 \}, \{ 0, 1 \})$ $7^{4} \mod 15 = 1 ↔ (\{ 1, 0 \}, \{ 0, 1 \}) + (\{ 1, 0 \}, \{ 1, 1 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$ $8^{2} \mod 15 = 4 ↔ (\{ 0, 0 \}, \{ 1, 1 \}) + (\{ 0, 0 \}, \{ 1, 1 \}) = (\{ 0, 0 \}, \{ 1, 0 \})$ $8^{2} \mod 15 = 2 ↔ (\{ 0, 0 \}, \{ 1, 0 \}) + (\{ 0, 0 \}, \{ 1, 1 \}) = (\{ 0, 0 \}, \{ 0, 1 \})$ $8^{2} \mod 15 = 1 ↔ (\{ 0, 0 \}, \{ 1, 1 \}) + (\{ 0, 0 \}, \{ 0, 1 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$ $9^{2} \mod 15 = 1 ↔ (\{ 0, 0 \}, \{ 1, 0 \}) + (\{ 0, 0 \}, \{ 1, 0 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$ $13^{2} \mod 15 = 4 ↔ (\{ 1, 0 \}, \{ 0, 1 \}) + (\{ 1, 0 \}, \{ 0, 1 \}) = (\{ 0, 0 \}, \{ 1, 0 \})$ $13^{3} \mod 15 = 7 ↔ (\{ 0, 0 \}, \{ 1, 0 \}) + (\{ 1, 0 \}, \{ 0, 1 \}) = (\{ 1, 0 \}, \{ 1, 1 \})$ $13^{4} \mod 15 = 1 ↔ (\{ 1, 0 \}, \{ 1, 1 \}) + (\{ 1, 0 \}, \{ 0, 1 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$ $14^{2} \mod 15 = 1 ↔ (\{ 1, 0 \}, \{ 0, 0 \}) + (\{ 1, 0 \}, \{ 0, 0 \}) = (\{ 0, 0 \}, \{ 0, 0 \})$